PEMANFAATAN BATOK KELAPA SEBAGAI MEDIA PEMBUATAN BIO-INSTRUMEN MUSIK - Surya Rahman; Rico Gusmanto (Besaung : Jurnal Seni Desain dan Budaya, 2021)
Bio-musical instruments can be defined as musical instruments made from plant wastes in the surrounding environment. One of the plant waste that is easily found in the community is coconut shell. Coconut shells are often overlooked for their use as a creative medium, especially in the field of music. Musical instruments are the main media for creativity in the art of music. The rise of musical instruments or musical instruments with high prices has become one of the inhibiting factors for young people to be creative in the field of music. Seeing this phenomenon, it is deemed necessary to develop people's creativity in making their own musical instruments at economical prices but still able to compete with manufactured musical instruments. In making this bio-instrument, the method used consists of problem identification, preparation, application, and evaluation. Through this method, the results obtained in the use of coconut shell waste into creative media are the Kalimba instrument played by plucking the iron keys as the source of the tone, while the coconut shell is used as the main medium for the sound resonance of the Kalimba instrument. Kalimba is classified into a type of lamellophone instrument, which is a musical instrument that has a tongue or a thin plate. In addition to the easy-to-use manufacturing process, the tools and materials in making these instruments are also easy to find and can even take advantage of used materials. The results of making bio-musical instruments are expected to become a reference and reference for academics and non-academics, regarding how to make musical bio-instruments using coconut shell waste. Keywords : Bio-Music Intrument, Coconut Shells, Kalimba